Evaluación de la colaboración científica en publicaciones periódicas del área de Biblioteconomía y Documentación. Documentación: España, 1975-1984 - Arquero Avilés, Rosario (Revista General de Información y Documentación, 2003)
Findings are given of scientific collaboration indicator of a production and citation analysis performed on library and information science serials during the period 1975-1984 in Spain. Results provide the number of authors in each work (in relation with the year of publication). In addition, for published works in selected library and information science serials, it’s showed the relation between the number of authors per work and the serial of publication. Finally, it’s determined institutional origin of authors in works with the greatest level of scientific collaboration.